Institutional congruence for resilience management in interdependent infrastructure systems. (June 2020) - Farahmand, Hamed; Dong, Shangjia; Mostafavi, Ali; Berke, Philip R.; Woodruff, Sierra C.; Hannibal, Bryce; Vedlitz, Arnold
Abstract: Institutions are important elements in human systems influencing interactions among organizations that contribute to resilience management in interdependent infrastructure systems (IISs). In particular, the existence of institutional congruence among actors across these complex systems is important for the successful operation of such systems. Institutional congruence is the extent to which organizations have similar, agreed upon, or harmonized institutions. Institutional congruence has remained an understudied aspect of the management of resilience in IISs. This paper assesses three significant aspects of resilience management of IISs through the evaluation of organizational institutions: organizations' involvement in hazard mitigation planning and use of hazard mitigation plans; organizations' view regarding the responsibility of hazard mitigations and contributors to hazard; and organizations' support of policies for hazard risk mitigation. Organizational institutions within a sector and across different sectors that are involved in hazard risk mitigation in the context of the Harris County during Hurricane Harvey were investigated. The impacts of the extent to which organizational institutions were congruent on the cooperative management of resilience and the vulnerability of infrastructures were discussed. Findings show that, although the use of non-structural solutions is supported by most of the organizations, the existing plans did not specifically focus on such solutions. Additionally, the results indicate the existence of congruence across sectors about the importance of responsibility sharing among governments at different levels in mitigating the risk of hazard. Different organizations across sectors have varying perceptions regarding suitable approaches for flood risk mitigation that contribute to the vulnerability of physical infrastructures. Highlights: Institutional congruence among stakeholders impacts the coordination of resilience management in IISs. Important components of resilience management examined: hazard mitigation planning, hazard contributors, and policy support. A stakeholder survey was conducted to assess institutional congruence in Harris County in the context of Hurricane Harvey. Institutional congruence regarding the importance of responsibility sharing among governments for hazard mitigation is shown. Organizations across sectors have varying perceptions regarding suitable approaches for mitigating the risk of flooding.